2020
DOI: 10.1016/j.pmedr.2020.101165
|View full text |Cite|
|
Sign up to set email alerts
|

Locations of licensed and unlicensed cannabis retailers in California: A threat to health equity?

Abstract: This study examined whether unlicensed and licensed cannabis retailers in California are disproportionately located in neighborhoods with minority populations or populations living below the Federal Poverty Level. We mapped the locations of licensed and unlicensed cannabis retailers in California in October 2018, combining advertisements from cannabis websites with licensing data. Demographic characteristics of neighborhoods with and without licensed and/or unlicensed cannabis retailers were compared. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…9,10 Communities of color (Black and Hispanic populations, as well as some Asian subgroups) may be more likely than White populations to experience negative consequences of legalization, including increased frequent cannabis use and CUD. 11 Such unintended consequences could occur because of structural factors informed by the legacies of US racism, for example locating dispensaries (which have been tied to increased CUD 12,13 ) in neighborhoods with a majority racial or ethnic minority population.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Communities of color (Black and Hispanic populations, as well as some Asian subgroups) may be more likely than White populations to experience negative consequences of legalization, including increased frequent cannabis use and CUD. 11 Such unintended consequences could occur because of structural factors informed by the legacies of US racism, for example locating dispensaries (which have been tied to increased CUD 12,13 ) in neighborhoods with a majority racial or ethnic minority population.…”
Section: Introductionmentioning
confidence: 99%
“…The estimates of our two cannabis measures, policy and accessibility, were inconsistent with findings on sales of blunt wraps in legalized 2 population size was used instead of population density because the latter could not be determined for unincorporated areas of a jurisdiction that are noncontiguous; 3 percent households receiving Supplemental Nutrition Assistance Program (SNAP) benefits; 4 includes some LTRs in jurisdictions that also restricted cannabis advertising (n = 202); 5 minimum pack size of five, ten or twenty LCCs; 6 percent difference in the increase (+) and decrease (-) in retail availability from 2016 to 2019; cannabis markets (Giovenco et al, 2018) and locations of cannabis retailers in California (Unger et al, 2020). Unger et al (2020) reported that among geographic service areas in California (2.5 mile radius), a higher percentage of those with a cannabis retailer were below the federal poverty line (18.1% vs. 12.9%, p < .001); LTRs in such areas frequently market and sell cigarillos. One might surmise that our unexpected finding was a function of the negative correlation between tobacco and cannabis restrictions in the jurisdictions where LTRs were sampled.…”
Section: Discussionmentioning
confidence: 99%
“…The locations of cannabis retailers throughout California were obtained by co-authors (JBU, ROV) who collected the data in October, 2018 as part of another study (Unger et al, 2020). Unger et al (2020) identified licensed retailers (n = 448) from the Bureau of Cannabis Control and unlicensed retailers (n = 662) from a comprehensive search of the websites weedmaps.com and leafly.com. Among the cannabis businesses with a retail location, 47 were excluded because they only sold cannabis for medicinal purposes, yielding 1063 cannabis retailers for the analysis.…”
Section: Cannabis Retailers and Accessibility Potentialmentioning
confidence: 99%
“…To better understand these trade-offs and improve equity within the cannabis industry, it is critical to know locations of both licensed and unlicensed outlets and how these locations have changed over time. Unger and colleagues examined whether licensed and unlicensed outlets were more common in high poverty and minority neighborhoods across California in 2018, the first year of legal cannabis sales (Unger et al 2020 ). In that year, unlicensed outlets were more common in Latinx neighborhoods in California, but no patterns were detected for licensed outlets (Unger et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unger and colleagues examined whether licensed and unlicensed outlets were more common in high poverty and minority neighborhoods across California in 2018, the first year of legal cannabis sales (Unger et al 2020 ). In that year, unlicensed outlets were more common in Latinx neighborhoods in California, but no patterns were detected for licensed outlets (Unger et al 2020 ). The present study builds on that analysis and adds to the sparse literature in this area by bolstering methods for identifying licensed and unlicensed outlets.…”
Section: Introductionmentioning
confidence: 99%